Effects of Crowd Size, Composition, and Noise Level On Pool Use in a Mixed-Species Penguin Colony - Ashley N. Edes (Animal Behavior and Cognition, 2021)
Studies on how visitors affect penguins in human care report a mixture of negative, neutral, and positive impacts on behavior and physiology. Swimming is a highly motivated behavior that may promote positive welfare in penguins. We investigated how visitor crowd size, composition, and noise levels impact pool use in a mixed-species colony housing king (Aptenodytes patagonicus; n = 20), gentoo (Pygoscelis papua; n = 14), and southern rockhopper (Eudyptes chrysocome; n = 24) penguins. We used video and sound loggers to record if penguins were on land or in water, the number of human adults and children present, and noise levels using 5-minute scan samples from 09:00-15:00 over 36 continuous days. Data were analyzed using linear mixed models with proportion of penguins in the water as the dependent variable and crowd size, composition, and noise levels in A-weighted (dBA) and C-weighted (dBC) scales as independent variables. Crowd size was positively associated with pool use in gentoo penguins. Crowd composition did not predict pool use in any species. Noise levels in dBA, which is adjusted to the higher frequencies of human hearing, positively predicted pool use in southern rockhopper penguins. Noise levels in dBC, which captures lower frequencies, did not predict pool use in any species. No evidence of negative visitor effects was observed. Instead, these results suggest visitors are a neutral stimulus to king penguins and may be enriching to gentoo and southern rockhopper penguins.